Mechanisms of Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
The prevailing theories of epileptogenesis are reviewed from the Departments of Neurology, Beth Israel Deaconess Medical Center, Boston, and the University of California San Francisco, CA.